PENGARUH KEPUASAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DI PT. ALFATIH INDO TEKNOLOGI CABANG KEDIRI - Khoirotun Ayuni, Zulfa Aulia; Rahma Ulfa Maghfiroh (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to examine the effect of job satisfaction and work motivation on employee performance at PT. Alfatih Indo Teknologi, Kediri branch. In the context of increasingly fierce business competition, improving employee performance has become a key factor in the success of a company. Therefore, this study is important to understand the factors that influence employee productivity and how these two variables can be utilized to improve organizational performance. The method used is a descriptive quantitative approach with Structural Equation Modeling (SEM) analysis. Data were collected through questionnaires distributed to 30 employees of PT. Alfatih Indo Teknologi Kediri, supported by secondary data from relevant literature. The results of the analysis show that both job satisfaction and work motivation have a positive and significant effect on employee performance. Specifically, job satisfaction has a greater influence than work motivation, with path coefficients of 0.613 and 0.147, respectively. The coefficient of determination (R²) of 0.501 indicates that approximately 50.1% of the variation in employee performance can be explained by these two variables. These findings emphasize the importance of improving the work environment, incentives, and motivation programs to increase employee productivity and well-being. The main conclusion of this study is that companies need to focus on improving job satisfaction as a strategy.